2020
DOI: 10.1080/19490976.2020.1745044
|View full text |Cite
|
Sign up to set email alerts
|

Skin exposure to sunlight: a factor modulating the human gut microbiome composition

Abstract: Background: The gut microbiome has been increasingly acknowledged as playing a pivotal role in human health. Therefore, a number of studies have focused on variables that impact its microbial structure and consequent functionality. A wide range of factors, such as diet, age, sex, life stage, behavior, ethnicity, and diseases have been considered, and strong links were set out. However, some aspects regarding the microbiome determinants are still under-explored. Discussion: Recently, Bosman et al. presented evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…After three rounds of ultraviolet radiation in a week, the alpha and beta diversities of bacteria in the intestinal tract of females increased, and the number of multiple bacterial genera changed ( Bosman et al, 2019 ). Furthermore, excessive ultraviolet radiation to the human body can lead to the emergence of intestinal flora in the thick wall of the phylum, increased deformation of the phylum, and a reduction in Bacteroides ( Conteville and Vicente, 2020 ). Ghaly et al (2018) found similar changes in the intestinal tract of mice exposed to high levels of ultraviolet light.…”
Section: Factors Affecting the Intestinal Flora In The Qinghai–tibet ...mentioning
confidence: 99%
“…After three rounds of ultraviolet radiation in a week, the alpha and beta diversities of bacteria in the intestinal tract of females increased, and the number of multiple bacterial genera changed ( Bosman et al, 2019 ). Furthermore, excessive ultraviolet radiation to the human body can lead to the emergence of intestinal flora in the thick wall of the phylum, increased deformation of the phylum, and a reduction in Bacteroides ( Conteville and Vicente, 2020 ). Ghaly et al (2018) found similar changes in the intestinal tract of mice exposed to high levels of ultraviolet light.…”
Section: Factors Affecting the Intestinal Flora In The Qinghai–tibet ...mentioning
confidence: 99%
“…All barrier organs, and, in particular, the skin are continuously challenged by the exposome (or the collection of all environmental factors impacting human health) which also impacts the microbiome in its composition and metabolism, exemplified by dietary intake, 27 environmental pollution 28 , 29 and UV exposure. 30 , 31 Epidemiological and experimental studies on exposome‐associated AHR ligands (eg certain pollutants and dietary compounds, or UV radiation‐generated endogenous tryptophan metabolites) and signalling thus need to consider the additional influence of exposome‐mediated alterations in the microbiome and changes in microbial‐derived AHR ligands thereof.…”
Section: Host Ahr Signalling Via Skin Microbiotamentioning
confidence: 99%
“…98 Narrowband UVB and natural sunlight exposure on the skin may even modulate the gut microbiome. 99,100 The skin, gut and household microbiome varies amongst populations living in regions with the same latitude, but varying levels of urbanization. These changes, particularly changes in the mycobiome, are associated with availability of household cleaning products and dwelling type.…”
Section: Skin Microbiome In Psoriasismentioning
confidence: 99%